2018
DOI: 10.1177/1363461517748813
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles and emerging adult depressive symptoms in Cebu, the Philippines

Abstract: Incidence of depressive disorders and symptoms increases during the transition to adulthood. The parenting relationship is a potential target for interventions to reduce risk for depression in offspring during this time period, and a four-category typology of parenting styles (authoritative, permissive, authoritarian, and neglectful) has been found to correlate with offspring psychological functioning. The majority of studies, however, have examined this four-category parenting style typology in Western popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…There are many other studies showing that permissive or authoritarian type of parenting style have a negative effect on children's grades, high internet usage among children, negative outcomes as anxiety, depression, substance misuse and behavioral problems in school. [12][13][14] Saunders et al study has shown that authoritative parenting style has inverse relation with physical activity. In the study it reflected authoritative parents provided high support to their children, making them non-active in terms of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…There are many other studies showing that permissive or authoritarian type of parenting style have a negative effect on children's grades, high internet usage among children, negative outcomes as anxiety, depression, substance misuse and behavioral problems in school. [12][13][14] Saunders et al study has shown that authoritative parenting style has inverse relation with physical activity. In the study it reflected authoritative parents provided high support to their children, making them non-active in terms of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the context of the Philippines, the impact of parenting styles often differs between sons and daughters [ 82 ]. Hock et al, [ 83 ] suggested that in the Philippines, parents tend to be stricter with daughters than sons, particularly concerning romantic relationships and sex [ 84 ], whereas the strictness of parents towards sons tended to focus on their educational and occupational achievements. A different parenting focus on sons and daughters may influence restrictions of freedom for girls and expectations for boys, and this may lead to the negative impact of parental involvement in suicidal behaviour outcomes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in the Philippines, emerging adulthood has been described as a period of expressing oneself, immersion in pop culture, increased consumption behaviors, engagement in travel, leisure, and sports, the pursuit of education and professional advancements, use of digital technologies and sociopolitical arrangements ( Velasco, 2020 ). Unlike their Western counterparts, whose emerging adulthood is characterized by emancipation from home ( Arnett, 2006 ), the lives of Filipino emerging adults remain close to and influenced by their parents and other family members ( Hock et al, 2018 ; Velasco, 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%